2014
DOI: 10.1083/jcb.201406140
|View full text |Cite
|
Sign up to set email alerts
|

Chibby promotes ciliary vesicle formation and basal body docking during airway cell differentiation

Abstract: In the early stages of cilia formation in the mouse airway epithelium, Chibby is recruited to the distal appendages of centrioles and is necessary for efficient ciliary vesicle formation and basal body docking at the apical cell membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
114
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(131 citation statements)
references
References 52 publications
17
114
0
Order By: Relevance
“…Failure in vesicle docking to distal ends of centrioles has been previously reported for components of distal appendages, such as Cep164 and Cep123, that serve as adaptors for the binding of vesicles to the distal ends (Schmidt et al, 2012;Sillibourne et al, 2013;Tanos et al, 2013;Burke et al, 2014;Joo et al, 2013;Ye et al, 2014). Our data show that WDR8 or Cep135 knockdown does not decrease the centriolar levels of Cep164 or Cep123.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Failure in vesicle docking to distal ends of centrioles has been previously reported for components of distal appendages, such as Cep164 and Cep123, that serve as adaptors for the binding of vesicles to the distal ends (Schmidt et al, 2012;Sillibourne et al, 2013;Tanos et al, 2013;Burke et al, 2014;Joo et al, 2013;Ye et al, 2014). Our data show that WDR8 or Cep135 knockdown does not decrease the centriolar levels of Cep164 or Cep123.…”
Section: Discussionsupporting
confidence: 53%
“…Distal appendage proteins, including Cep164 and Cep123 (also known as Cep89), have been reported to be indispensable for this initial step of ciliary membrane biogenesis (Schmidt et al, 2012;Tanos et al, 2013;Joo et al, 2013;Sillibourne et al, 2013;Burke et al, 2014;Ye et al, 2014). Moreover, a cascade of small GTPases regulates vesicle docking and fusion at the mother centriole.…”
Section: Introductionmentioning
confidence: 99%
“…The mother centrioles are distinguished from immature daughter centrioles by the presence of accessory structures, including the subdistal and distal appendages at their distal end. While the subdistal appendages anchor cytoplasmic microtubules, the distal appendages (also called "transition fibers" at the ciliary base) are thought to be critical for the recruitment of small vesicles and subsequent docking of basal bodies to the plasma membrane (5)(6)(7)(8). Since no protein synthesis occurs in cilia, ciliary proteins are transported from the cell body via polarized vesicle trafficking (9,10).…”
mentioning
confidence: 99%
“…[18][19][20][21][22] More recently, we demonstrated that, during differentiation of airway ciliated cells, Cby1 localizes to nascent centrioles and interacts with Rabin8, a guanine nucleotide exchange factor (GEF) for the small GTPase Rab8 to promote Rab8 recruitment for efficient assembly of membranous structures, called ciliary vesicles, at the distal end of centrioles. 18 Intriguingly, Rab8 has been shown to regulate cell shape, and expression of dominant-negative Rab8 mutants or depletion of Rab8 by small interfering (si) RNAs promotes an epithelial cell-like morphology including tight cell-cell contacts and actin stress fiber formation. 37 Therefore, it is possible that Cby1 K D suppresses Rab8 activity, leading to MET-like changes, independent of or in parallel to its association with b-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…Cby1 also plays a crucial role during ciliogenesis, likely independent of b-catenin signaling. [18][19][20][21][22] Using human colon adenocarcinoma SW480 cells in which APC is mutated, we reported that stable expression of wildtype Cby1, but not a 14-3-3-binding-defective mutant (Cby1S20A), results in cytoplasmic translocation of b-catenin, concomitant with a reduction in b-catenin signaling and cell growth. 23 These results suggest a role for Cby1 as a tumor suppressor in colon cancer.…”
Section: Introductionmentioning
confidence: 99%